2020
DOI: 10.1038/s41598-020-68959-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of hepatitis E virus induces pancreatic necroptosis in miniature pigs

Abstract: infection by hepatitis e virus (HeV) via the oral route causes acute hepatitis. extra-hepatic manifestations of HeV infection may stem from various causes; however, its distribution in organs such as the liver, as well as the mechanisms underlying HeV-induced cell injury, remain unclear. the objective of this study was to determine the chronological distribution of HeV in various tissues of HeV-challenged miniature pigs and to investigate the mechanisms underlying HeV-induced cell death in the pancreas and liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 54 publications
(71 reference statements)
1
28
0
1
Order By: Relevance
“…Recently the role of immune cells in the spread of HEV infection to various body organs has been studied. Immune cells are permissive to HEV and help the virus enter various body organs, as shown in vivo and in vitro studies [ 165 , 166 ]. It is possible that this may be one of the ways in which the virus reaches the maternal–fetal interface and causes vertical transmission.…”
Section: Proposed Hypothesis On Pathogenesis Of Mortality In Hev-infected Pregnant Womenmentioning
confidence: 99%
“…Recently the role of immune cells in the spread of HEV infection to various body organs has been studied. Immune cells are permissive to HEV and help the virus enter various body organs, as shown in vivo and in vitro studies [ 165 , 166 ]. It is possible that this may be one of the ways in which the virus reaches the maternal–fetal interface and causes vertical transmission.…”
Section: Proposed Hypothesis On Pathogenesis Of Mortality In Hev-infected Pregnant Womenmentioning
confidence: 99%
“… 113 HEV may replicate in the immune cells circulating and/or residing in the lymph node such as T‐lymphocytes, B‐lymphocytes, plasma cells and macrophages. Jung and colleagues recently showed that HEV enters various organs via the immune cells 114 . They also reported that the lymphoid tissues of miniature pigs have the highest amounts of HEV antigens 114 …”
Section: Hematological Manifestations Associated With Hev Infectionmentioning
confidence: 99%
“…Jung and colleagues recently showed that HEV enters various organs via the immune cells 114 . They also reported that the lymphoid tissues of miniature pigs have the highest amounts of HEV antigens 114 …”
Section: Hematological Manifestations Associated With Hev Infectionmentioning
confidence: 99%
See 2 more Smart Citations